Privacy Management in the Digital Era: Managing Instagram Close Friends Feature Among Lampung University Students - Azis, Diky Luqman; Windah, Andi; Nurhaida, Ida (Universitas Islam Negeri Raden Intan Lampung, 2024)
Concerns about personal information leakage have been growing alongside the ease with which personal data is shared on social media platforms. Instagram's